PENGARUH MEDIA FUN THINKERS BOOK TERHADAP HASIL BELAJAR SISWA PADA MATERI NORMA DALAM KEHIDUPANKU KELAS V SD NEGERI LAMPEUNEURUT KABUPATEN ACEH BESAR - Nurur Rahmah; Aida Fitri; Nurmasyitah (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This research was motivated by the lack of use of interactive learning media, which resulted in low student learning outcomes on the topic “Norms in My Life” in grade V at SD Negeri Lampeuneurut. The research problem in this study was whether there was an effect of the Fun Thinkers Book media on students’ learning outcomes on the topic “Norms in My Life” in grade V at SD Negeri Lampeuneurut. This study aimed to determine the effect of the Fun Thinkers Book media on students’ learning outcomes on the topic “Norms in My Life” in grade V at SD Negeri Lampeuneurut.This study used a quantitative approach with a quasi-experimental method and a nonequivalent control group design. The research subjects consisted of 50 students divided into an experimental class and a control class. The experimental class was taught using the Fun Thinkers Book media, while the control class used learning video media. Data were collected through pretest and posttest. Data analysis included the N-gain score test, normality test, and hypothesis testing using the Mann-Whitney test.The results showed that the average N-gain score of the experimental class was 77%, categorized as effective, while the control class obtained 37%, categorized as ineffective. The Mann-Whitney test showed an Asymp. Sig. (2-tailed) value of 0.001 < 0.05. Therefore, it can be concluded that there was a significant effect of the Fun Thinkers Book media on students’ learning outcomes on the topic “Norms in My Life” in grade V at SD Negeri Lampeuneurut. Keywords: Fun Thinkers Book, learning outcomes, Norms in My Life.